Curcumin-like Compound Inhibits Proliferation of Adenocarcinoma Cells by Inducing Cell Cycle Arrest and Senescence - Rafael Fonseca; Yasmin dos Santos Louzano; Cindy Juliet Cristancho Ortiz; Matheus de Freitas Silva; Maria Luiza Vieira Felix; Guilherme Álvaro Ferreira-Silva; Ester Siqueira Caixeta; Bruno Zavan; Claudio Viegas; Marisa Ionta (Pharmaceuticals)
Background: Lung cancer is the leading cause of cancer-related death in the male sex worldwide. Non-small cell lung cancer (NSCLC) is the most prevalent type, accounting for 80–85% of cases, and lung adenocarcinoma is the most common and lethal NSCLC subtype, being responsible for ca. 50% of deaths. Despite new therapeutic strategies, lung cancer mortality rates remain high, highlighting the need for the development of new drugs. Objectives: We investigated the pharmacological potential of a series of curcumin-like compounds using two lung adenocarcinoma cell lines as models. Methods and Results: Cell viability assay led to the identification of PQM-214 as the hit compound, and other methodologies were employed to investigate the mechanisms underlying its antitumor potential, including cell cycle analysis, mitotic index determination, assessment of clonogenic capacity, senescence-associated β-galactosidase and annexin V assays, quantitative PCR, and Western blot analyses. The mechanism of action of PQM-214 was investigated in A549 cells, revealing that it effectively inhibits cell proliferation by inducing cell cycle arrest, apoptosis, or senescence. Cell cycle key regulators were significantly modulated by PQM-214, with cyclin E2, MYC, and FOXM1 being downregulated, while senescence markers such as cyclin D1, CDKN1A (p21), IL-8, TIMP1, and TIMP2 were upregulated. Moreover, Western blot results revealed upregulation of cyclin D1 and p21 in PQM-214-treated samples, with a downregulation of cyclin B. Conclusions: PQM-214 seems to act on different molecular targets in lung adenocarcinoma cells, inhibiting cell proliferation and inducing apoptosis. Further studies will be conducted to explore whether PQM-214 can also act as a senolytic agent, which would reinforce its anticancer potential.